Inhibitor of Cysteine Protease of Plasmodium malariae Regulates Malapains, Endogenous Cysteine Proteases of the Parasite - Hương Giang Lê; Jung-Mi Kang; Tuấn Cường Võ; Thảo Dương Nguyễn; Myunghwan Jung; Min Kyoung Shin; Won Gi Yoo; Byoung-Kuk Na (Pathogens, 2022)
Cysteine proteases of malaria parasites have been recognized as potential targets in antimalarial drug development as they play pivotal roles in the biology of these parasites. However, strict regulation of their activities is also necessary to minimize or prevent deleterious damage to the parasite and the host. Previously, we have characterized falcipain family cysteine proteases of Plasmodium malariae, named as malapains (MPs). MPs are active hemoglobinases. They also may participate in the release of merozoites from mature schizonts by facilitating remodeling of erythrocyte skeleton proteins. In this study, we identified and characterized an endogenous inhibitor of cysteine protease of P. malariae (PmICP). PmICP shared similar structural and biochemical properties with ICPs from other Plasmodium species. Recombinant PmICP showed a broad range of inhibitory activities against diverse cysteine proteases such as falcipain family enzymes (MP-2, MP-4, VX-3, VX-4, and FP-3), papain, and human cathepsins B and L, with stronger inhibitory activities against falcipain family enzymes. The inhibitory activity of PmICP was not affected by pH. PmICP was thermo-labile, resulting in rapid loss of its inhibitory activity at a high temperature. PmICP effectively inhibited hemoglobin hydrolysis by MPs and regulated maturation of MPs, suggesting its role as a functional regulator of MPs.